2001
DOI: 10.1095/biolreprod65.4.979
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Fas Ligand Expression by Estradiol and Progesterone in Human Endometrium1

Abstract: Implantation involves a complex set of events, including apoptosis in endometrial cells. Apoptosis in human endometrium coincides with the implantation window, suggesting a potential role for steroid hormones in its regulation. Fas ligand (FasL) is one of the mediators of apoptosis in differentiated cells and in embryonic development. Interaction of FasL with its receptor, Fas, induces apoptosis through autocrine and paracrine signaling. We hypothesized that FasL expression in human endometrium is cycle-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 24 publications
2
54
0
2
Order By: Relevance
“…Many factors, for example IL8, vascular endothelial growth factor (VEGF), chemokine ligand 2 (CCL2), various components of the extracellular matrix, the early embryonal signal hCG as well as the hormones progesterone and estradiol, have been shown to regulate FasL in human ESCs (Harada et al, 2004;Kayisli et al, 2003;Selam et al, 2001). So far, the expression of FasL by ESCs has been interpreted as a mechanism to regulate the population of immune cells present at the implantation site, thereby mediating immune tolerance in respect to the trophoblast.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors, for example IL8, vascular endothelial growth factor (VEGF), chemokine ligand 2 (CCL2), various components of the extracellular matrix, the early embryonal signal hCG as well as the hormones progesterone and estradiol, have been shown to regulate FasL in human ESCs (Harada et al, 2004;Kayisli et al, 2003;Selam et al, 2001). So far, the expression of FasL by ESCs has been interpreted as a mechanism to regulate the population of immune cells present at the implantation site, thereby mediating immune tolerance in respect to the trophoblast.…”
Section: Discussionmentioning
confidence: 99%
“…RCAS1 has been recognized to play a role in immune evasion of the tumor cells. Selam et al [83] showed up-regulation of FasL in human endometrium by estradiol and progesterone. Kasyisli et al [30] demonstrated that hCG stimulates FasL mRNA and protein in endometrial cells, and observed that cells of early pregnancy deciduas express strong FasL immunoreactivity.…”
Section: Fas Ligand Expressionmentioning
confidence: 99%
“…Its ligand (Fas-L/ CD178) is a 37 kDa protein belonging to the superfamily of the TNFs [20][21][22][23] . Fas and Fas-L are engaged in the cell death process; after the interaction of Fas-L on the cell surface with the Fas receptor, there is formation of aggregates in the form of trimers, which bond to adaptor protein FADD (Fas associated death domain) present in the cytoplasm.…”
Section: Apoptosis Activation Pathwaysmentioning
confidence: 99%